The Logistic‐Exponential Weibull Model as a Tool to Predict Natural Microflora Inactivation of Agave Mapsiaga Aguamiel (Agave Sap) by High Pressure Treatments. Issue 2 (6th May 2016) - Serment‐Moreno, Vinicio; Franco‐Vega, Avelina; Escobedo‐Avellaneda, Zamantha; Fuentes, Claudio; Torres, José Antonio; Dibildox‐Alvarado, Elena; Welti‐Chanes, Jorge
Abstract: Agave sap (aguamiel) is a major source of nutraceutics that may be affected by natural microflora fermentation and thermal processing. High pressure processing (HPP) at 100–400 MPa/25C/1–20 min was investigated as an alternative non‐thermal pasteurization by analyzing aerobic mesophiles (AM), coliforms (CL) and yeasts and molds (YM) inactivation. Standard statistics and information theory criteria determined the goodness of fit of first‐order kinetics (LKM), Weibull (WBLL) and Gompertz (GMPZ) models. Non‐detectable CL were found for 300 MPa/1 min, whereas 400 MPa/4 min HPP treatments reduced AM and YM by 3.86–4.72 log10 units. Statistical analysis showed WBLL best described microbial inactivation. A secondary WBLL model consisting of logistic‐exponential b ′( P ) and exponential decay n ( P ) functions predicted AM ( R 2  = 0.835), YM ( R 2  = 0.867) kinetics for different pressure–time combinations. The secondary WBLL model predicted commercial HPP pasteurization conditions (5‐log10 reductions of AM and YM) could be achieved at 400 MPa/5 min or 500 MPa/2 min. Practical Applications: High pressure processing (HPP) is a consumer preferred alternative for food pasteurization. Aside from guacamole and some fruit and vegetable juices, there no other significant HPP foods available in México. Our research group believes that the commercialization of food products based on endemic plants such as agave sap (aguamiel), will draw the attention of national and international consumers, researchers and industrial HPP food processors to increase the number of HPP applications. Furthermore, the development of reliable pressure–time predictive models for microbial inactivation would help HPP food processors to ensure food safety and generate better budget estimates for novel products, or redefine current operating conditions since processing costs depend on the applied pressure level and pressure holding time.